Initial state of DNA-Dye complex sets the stage for protein induced fluorescence modulation - Rashid, Fahad; Raducanu, Vlad-Stefan; Zaher, Manal S.; Tehseen, Muhammad; Habuchi, Satoshi; Hamdan, Samir M. (Nature communications, 2019)
Protein-induced fluorescence enhancement (PIFE) is a popular tool for characterizing protein-DNA interactions. PIFE has been explained by an increase in local viscosity due to the presence of the protein residues. This explanation, however, denies the opposite effect of fluorescence quenching. This work offers a perspective for understanding PIFE mechanism and reports the observation of a phenomenon that we name protein-induced fluorescence quenching (PIFQ), which exhibits an opposite effect to PIFE. A detailed characterization of these two fluorescence modulations reveals that the initial fluorescence state of the labeled mediator (DNA) determines whether this mediator-conjugated dye undergoes PIFE or PIFQ upon protein binding. This key role of the mediator DNA provides a protocol for the experimental design to obtain either PIFQ or PIFE, on-demand. This makes the arbitrary nature of the current experimental design obsolete, allowing for proper integration of both PIFE and PIFQ with existing bulk and single-molecule fluorescence techniques. Protein-induced fluorescence enhancement (PIFE) is a popular tool for characterizing protein-DNA interactions. Here, authors provide a perspective on understanding the general phenomenon of induced fluorescence modulation